Virtuous Legislation: The Royal Decree for the Sustainable Management of the Woods of Serra San Bruno, Stilo, Mongiana, and Ferdinandea - Ghezzi, Renato; Fiorenza, Elia (European Scientific Journal, ESJ, 2024)
The extraction and processing of metals in the Calabrian Serre region have ancient origins, with Greek colonies utilizing local mines for tools and coins. The Normans later granted mines to Carthusian monks, enhancing military production. Ferdinand II's reign saw the peak of the Ferdinandea foundry, leading to its designation as a military colony. The region's steel complex became a European industrial hub. In the 18th century, laws were enacted to balance industrial needs with environmental protection. The Salvaboschi Decree of 1773, issued by the Bourbons and King Ferdinand IV, aimed to protect the forest heritage by implementing forty-year cutting cycles. It regulated tree selection and cutting height to promote forest regeneration, representing a significant step towards sustainable forest management in the Calabrian Serre region.